Strengthening Character Education through Daily Habituation Activities - Wandira, Ayu; Muharam, Agus (International Conference on Elementary Education, 2022)
This study aims to explore and examine information about strengthening character education through daily habituation activities. The method used in this research is literature study. Character education as one of the most important aspects in creating quality human resources must be instilled from a basic age through daily habituation activities, so that students have a strong foundation in social life. Character education is the process of changing the attitude, psychology, morals, character of a person or group of people to become a mature person. The goal of character education basically is to form a strong characteristic, competitive, noble, moral, tolerant, cooperative, patriotic, dynamically developed, oriented to science and technology which are based by faith and piety to God Almighty and also based on Nation ideology that is Pancasila. Character education is directed to emphasize certain values such as: religious, honest, independent, fair, caring, responsible, polite, and others. In order to help students understand, interpret, and practice these values into everyday life to make it easier to achieve successful life.